APLIKASI INDUKSI MUTASI UNTUK PEMULIAAN TANAMAN HIAS - Endang Gati Lestari (BERITA BIOLOGI, 2021)
ABSTRACTThe breeding of ornamental plants through mutation induction has been applied to obtain the desired new characters. High diversity, such as brighter colors, more attractive shapes, and aromas, are needed for the assembly of new high-yielding varieties to increase sales value. Mutagens that can be used as agents for mutation induction are physical mutagens (gamma rays, x rays, beta rays, UV rays) and chemical mutagens (EMS, DES, colchicine, oryzalin). The mutagens have been implemented to obtain a superior character compared to its parents. Breeding of ornamental plants through mutation has been applied in various countries such as Japan, Thailand, Korea, the Netherlands, and Indonesia to produce many new varieties, comprising of chrysanthemums, roses, gladiolus, tulips, carnations, etc. The resulting new characteristics include a change in color to become more attractive according to market tastes, the shape and petals of a single flower that was originally single, becoming stacked, and not easily wither. The purpose of writing this review is to provide information about the role of mutations in the formation of new varieties in ornamental plants as well as mutagens that able to be utilized both physically and chemically.  ion has been applied to obtain the desired new characters. High diversity, such as brighter colors, more attractive shapes, and aromas, are needed for the assembly of new high yielding varieties to increase sales value. Mutagens that can be used as agents for mutation induction are physical mutagens (gamma rays, x rays, beta rays, UV rays) and chemical mutagens (EMS, DES, colchicine, oryzalin). The mutagens have been implemented to obtain a superior character compared to its parents. Breeding of ornamental plants through mutation has been applied in various countries such as Japan, Thailand, Korea, the Netherlands, and Indonesia to produce many new varieties, comprising of chrysanthemums, roses, gladiolus, tulips, carnations etc. The resulting new characteristics include a change in color to become more attractive according to market tastes, the shape and petals of a single flower that were originally single, become stacked, and not easily wither. The purpose of writing this review is to provide information about the role of mutations for the formation of new varieties in ornamental plants as well as mutagens that able to be utilized both physically and chemically. Key words: in vitro culture, somaclonal variation, mutase ABSTRAK Pemuliaan pada tanaman hias melalui induksi mutasi telah diaplikasikan untuk mendapatkan karakter baru yang diinginkan. Keragaman yang tinggi seperti warna menjadi lebih cemerlang, bentuk dan aroma lebih menarik sangat diperlukan untuk perakitan varietas unggul baru sehingga meningkatkan nilai jual. Mutagen yang dapat digunakan sebagai agen untuk induksi mutasi adalah mutagen fisik (sinar gamma, sinar x, sinar beta, UV) dan mutagen kimia (EMS, DES, kolkisin, oryzalin), mutagen tersebut telah diaplikasikan untuk mendapatkan karakter yang lebih unggul dibanding tetuanya. Pemuliaan pada tanaman hias melalui mutasi telah dilakukan diberbagai negara seperti Jepang, Tailand, Korea, Belanda termasuk di Indonesia untuk menghasilkan banyak varietas baru antara lain pada krisan, mawar, gladiol, tulip, anyelir dll. Sifat baru yang dihasilkan antara lain perubahan pada warna menjadi lebih menarik sesuai selera pasar, bentuk dan kelopak bunga yang semula tunggal, menjadi bertumpuk, serta menjadi tidak mudah layu. Tujuan penulisan review ini adalah untuk memberikan informasi peran mutasi untuk pembentukan varietas baru pada tanaman hias serta mutagen baik fisik maupun kimia yang dapat digunakan.